Pengembangan E-Book Kimia Berbasis Augmented Reality (AR) pada Materi Bentuk Molekul - Ariska, Nasya Nur; Sholeh, Moh Ismail; Laksono, Pandu Jati (Chemistry Education Department of Education and Teaching Faculty, 2023)
This study was motivated by the limited support of engaging media in chemistry learning on molecular shape materials. The material of molecular shape is abstract and requires a medium capable of visualizing the molecular shape clearly and realistically. The technology that aligns with these problems is Augmented Reality. This research aims to observe the validity results of the developed product and to know the student's responses towards the Augmented Reality (AR) Based Chemistry E-book on Molecular Shape Material. This study is an R&D (Research and Development) development study. By using the 4-D development model that was modified into 3 stages; define, design, develop. The validation test of this media is based on assessments from language experts, media experts, and material experts. The product validation results were assessed by media experts by 97%, material experts by 94%, and language experts by 90%, with a very valid category. In addition, a trial was conducted on students to find out the response to the developed media. Based on the assessment results of student responses, a percentage of 89% was obtained on a small scale and 95% on a medium scale with a very good category